Spatial and temporal dynamics of phytoplankton assemblages in selected reaches of the upper river Mississippi River : Navigation pools 8, 13, and 26 - Manier, John T. (My University, 2014)
Phytoplankton are a critical component of large river food webs and they provide large quantities of organic carbon and biomolecules that sustain large river ecosystems. Relatively few studies have examined large-scale patterns in phytoplankton community composition in the Upper Mississippi River (UMR). The purpose of this study was to examine the spatial and temporal dynamics of phytoplankton community composition across diverse aquatic areas of the UMR, and to investigate factors affecting phytoplankton community composition and, in particular, the abundance of blue-green algae. Data included in this study were derived from phytoplankton and water quality samples collected during the summer months of 2006-2009 from the main channel, backwater, and impounded areas of navigation pools 8 and 13, and from the main channel of pool 26. Forty-seven genera of phytoplankton were identified in the samples analyzed. The three most abundant genera included Aulacoseira, Aphanizomenon, and Microcystis. Phytoplankton community composition differed among aquatic areas and pools. The main channel and backwaters were dominated by a mixture of cyanobacteria and diatoms, however the main channel also displayed large abundances of green algae, while the backwaters were typified by flagellated species (i.e., cryptomonads and euglenoids). The impounded areas were similar to the backwaters, but exhibited a greater proportion of cyanobacteria. With respect to longitudinal changes in phytoplankton community composition, the main channels of P8 and P13 could be dominated by either cyanobacteria or diatoms (depending on conditions), while P26 was always dominated by diatoms. Phytoplankton community composition was strongly influenced by discharge. In navigation pools 8, 13, and 26, taxonomic richness tended to increase with increasing discharge (possibly reflecting recruitment from off-channel areas and scouring of the periphyton). Moreover, the main channel communities of pools 8, 13, and 26 became more similar during high discharge years. Surprisingly, cyanobacteria were dominant in the main channel of P8 and P13 during the highest discharge year (2008). This pattern was unexpected, yet pronounced. This may be due to a variety of factors, including greater availability of a limiting nutrient that we did not analyze (i.e. iron) or recruitment from off-channel areas. The major finding of this study was the prominence of cyanobacteria in the UMR. Cyanobacteria were present in 204 of 224 samples (96%). In addition, 1 in every 10 of my samples could be classified as having a moderate to severe cyanobacteria bloom (Kasich et al. 2013). There were no linear correlations between cyanobacteria total or proportional biovolume and selected covariates (including nitrogen and phosphorus). Instead, most cyanobacteria communities clustered around moderate nutrient concentrations, indicating that nutrient limitation was not a major driver of the patterns in cyanobacterial abundance. Phytoplankton communities were more likely controlled by physical factors, such as discharge, turbidity and residence time.
Keywords: Cyanobacteria; Phytoplankton--Mississippi River